EFEKTIVITAS METODE EKSPOSITORI DENGAN COOPERATIVE INTEGRATED READING AND COMPOSITION TERHADAP HASIL BELAJAR MAHASISWA SEMESTER SATU FKIP UHN TAHUN AJARAN 2013/2014 PADA POKOK BAHASAN STOIKIOMETRI - Erna Helena M Tampubolon (Pascasarjana Universitas Negeri Medan, 2014)
Abstract This study aims to determine which method is more effective is used for the Ekspositori method with the method of Cooperative Integrated Reading and Composition on that matter of stoichiometry in prodi mathematics pedagogy UHN. The hypothesis of this research is the existence of significant differences between the learning outcomes of students who use the Ekspositori method with the method of Cooperative Integrated Reading and Compositon on stoichiometric materials in mathematics pedadogy UHN prodi. The Data were processed using the test of normality test with Liliefors. It turns out that the results obtained from the normal Gaussian with Ekspositori Group = 5% and dk = 7 then Lhit = 0,1097 = 0,300 Ltab < as well as data that uses the methods of Cooperative Integrated Reading and Composition are also Gaussian normal with = 5% and dk = 9 then Lhit = 0,1337 = 0,273 Ltab <. To find out if the data comes from the population that bervarians same or different, then used its homogeneity test, apparently retrieved Fhit (1,417) < F ¬ tab (1,668) and thus, the population was homogeneous. to find out whether there are differences in the learning results using the method Ekspositori and the method of Cooperative Integrated Reading and Composition used t test, if k = 88 apparently retrieved thit (3,051) > ttab (1,991). Data analysis results obtained from equivalent and Byway of baku Experimental group of learning outcomes = 11,91 and raw = 2,932 Byway, in the control group = raw Byway and 10.20 = 2,455.Key words: The method Ekspositori, method of Cooperative Integrated Reading and Composition, Learning Achievement, Stoichiometry